Star Wars Episode III Revenge of the Sith - Lucas, George; McCallum, Rick; McGregor, Ewan; Portman, Natalie; Christensen, Hayden; McDiarmid, Ian; Jackson, Samuel; Lee,Christopher; Lucasfilm ltd.; Twentieth Century Fox. (San Francisco, California Lucasfilm Ltd, 2005)
Torn between loyalty to his mentor, Obi-Wan Kenobi, and the seductive powers of the Sith, Anakin Skywalker ultimately turns his back on the Jedi. This begins his complete journey to the dark side and his transformation into Darth Vader.
Starring Ewan McGregor, Natalie Portman, Hayden Christensen, Ian McDiarmid, Samuel L. Jackson, Christopher Lee; co-starring Anthony Daniels, Kenny Baker, Frank Oz.
Dolby Digital.
Printed and exclusively distributed by Viva Video, Inc.